2017
DOI: 10.1123/jsr.2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Muscle Activation Levels During the Push-Up-Plus Exercise on Stable and Unstable Surfaces

Abstract: The aim of this study was to evaluate the acute effect of the use of stable and unstable surfaces on electromyography (EMG) activity and coactivation of the scapular and upper-limb muscles during the push-up plus (with full protraction of the scapula). Muscle activation of anterior deltoid (AD), posterior deltoid (PD), pectoralis major, biceps brachii (BB), triceps brachii (TB), upper trapezius (UT), middle trapezius (MT), lower trapezius (LT), and serratus anterior (SA) levels and coactivation index were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…Seven articles discussed the effects of PUP variations (eg, different upper extremity, 31,47,48,50 lower extremity, 29,49 and PUP 8 positions) on training the SA and UT. Eleven articles 9,[15][16][17][18][19][20][21][22][23]52 focused on the effects of the base of support for PUP exercises. From our systematic review, we determined a suitable exercise prescription for training the SA and UT using PUP variations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven articles discussed the effects of PUP variations (eg, different upper extremity, 31,47,48,50 lower extremity, 29,49 and PUP 8 positions) on training the SA and UT. Eleven articles 9,[15][16][17][18][19][20][21][22][23]52 focused on the effects of the base of support for PUP exercises. From our systematic review, we determined a suitable exercise prescription for training the SA and UT using PUP variations.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve articles focused on the effects of the base of support during PUP exercises. 9,[15][16][17][18][19][20][21][22][23]51,52 After further checking for the meta-analysis, 1 article was excluded due to insufficient data for the means and standard deviations. 51 Therefore, 11 articles were included in this meta-analysis for analyzing the differences in SA and UT muscle activity during the PUP performed on stable and unstable surfaces.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is likely because elbow rocking is possible during the CKCUES test. Torres et al [32] showed no significant difference in muscle activity of TB with or without a stable surface during pushup plus. Lehman et al [33] showed that due to the mechanical advantage of TB in forearm length, responding to changes in stability during push-ups may be difficult.…”
Section: Discussionmentioning
confidence: 92%
“…1,2 SA muscle weakness leads to changes in the movement of the scapula, resulting in shoulder pain 3,4 and delayed movement, 5 being one of the causes of scapular dyskinesis. 6 Therefore, scapular protraction exercises have been suggested for weakness of SA, [5][6][7] as a way to strengthen it. Previous studies have mentioned that scapular protraction exercises are effective in increasing SA muscle activity.…”
Section: Introductionmentioning
confidence: 99%